Using Mathematical Poetry to Enhance Students’ Interest in Learning Mathematics by Leveraging Linguistic Intelligence - Mumtazah, Nadia Wardah; Asih, Endang Cahya Mulyaning (Jurnal Pendidikan MIPA, 2024)
Using Mathematical Poetry to Enhance Students’ Interest in Learning Mathematics by Leveraging Linguistic Intelligence. Objective: Mathematics is often perceived as challenging and anxiety-inducing, leading to low student interest and motivation. This study explores the potential of mathematical poetry as a teaching material to enhance students' interest in learning mathematics by leveraging linguistic intelligence. Linguistic intelligence, which involves the effective use of language, has been shown to positively influence mathematical understanding and problem-solving abilities. Methods: This study used a mixed-method approach with a sequential explanatory design involving 65 junior high school students from various schools in Indonesia. A mathematical poetry e-book was developed and validated as a teaching tool, followed by the distribution of learning interest questionnaires and interviews to collect data on student engagement. Findings: The findings indicate that using mathematical poetry significantly increased students' interest in learning mathematics, with the overall interest level being very high. The poetry's ability to convey emotions and vivid imagery through linguistic elements such as diction, figures of speech, and thematic depth played a crucial role in capturing students' attention and fostering a positive learning environment. Students expressed excitement, joy, and a deeper connection to the material when mathematical concepts were presented through poetry. However, the study also noted that the effectiveness of this approach varies depending on students' linguistic intelligence, with some students needing more language skills to connect with the material. Conclusion: The study concludes that integrating mathematical poetry into mathematics teaching can be an innovative and effective strategy to enhance students' interest and motivation, ultimately improving their mathematical abilities. Further research is recommended to explore the long-term impact of this approach and its applicability across different educational contexts.         Keywords: students’ learning interest, mathematical poetry, linguistic intelligence.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp554-568